The Role of Dairy Farmers in Surveillance and Control Program of Brucellosis in Bogor Regency - Heris Kustiningsih; Etih Sudarnika; Amiruddin Saleh; Chaerul Basri; Mirnawati Sudarwanto (Jurnal Sain Veteriner, 2023)
Brucellosis is an infectious and zoonotic disease that causes a negative impact on the health and economy of people in almost all countries. The prevalence of brucellosis in several regions in Indonesia is still quite high. The purpose of this study was to analyze the role of farmers in the brucellosis control and surveillance program in Bogor Regency. The study was conducted through a survey of 151 farmers in Bogor Regency from May to July 2022. A total of 68.9% of respondents are aged 25-50 years with an education level of 69.8% are low educated (Elementary School, Junior High School) and not in school . The experience of raising more than five years (58.2%) with the number of dairy cattle ownership is less than five heads, namely 41.7%. The brucellosis prevention practices that need to be improved are related to the use of disinfectants when cleaning the cage, livestock group management practices (separating pregnant cows from other cows, separating cows with suspected brucellosis from other healthy cows, separating newly purchased cows for two weeks before being merged with cows). long in the cage). The practice of brucellosis control that needs to be improved is proper handling of the placenta and cows infected with brucellosis properly. Surveillance practices that need to be improved are the practice of recording and reporting cases of miscarriage in the final trimester. After identifying farmer practices, it is very important to plan interventions in the form of training with a curriculum that refers to the level of farmer practice that is still lacking. It is hoped that by conducting training interventions for farmers, the level of knowledge of farmers will increase and the level of practice of farmers will also increase.